Book Reviews (The Muslim world, 1985)
Book reviewed in this article: Palestinian Rights: Affirmation and Denial. Edited by Ibrahim Abu-Lughod A Mediterranean Society: The Jewish Community of the Arab World as Portrayed in the Documents of the Cairo Geniza, Volume 4: Daily Life. By S. D. Goitein The Arabic Book. By Johannes Pedersen The Early Islamic Conquests. By Fred McGraw Donner The Islamic Impact. Edited by Yvonne Yazbeck Haddad, Byron Haines and Ellison Findly Persian Miniature Painting: and its Influence on the art of Turkey and India [The British Library Collections]. By Norah M. Titley Essays in Islamic Art and Architecture [Islamic Art and Architecture, Vol. I]. Edited by Abbas Daneshvari Architecture and Community: Building in the Islamic World Today. [The Aga Khan Award for Architecture.] Edited by Renata Holod with Darl Rastorfer Islam and Ownership. By Seyyed Mahmood Taleqani Society and Economics in Islam: Writings and Declarations of Ayatullah Sayyid Mahmud Taleghani. Translated from the Persian by R. Campbell Equality, Efficiency, and Property Ownership in the Islamic Economic System. By Akhtar A. Awan. Lanham Crime and Corrections: An Al-Islamic Perspective. By Sidney R. Sharif The Qur'ān and Its Interpreters. Vol. I. By Mahmoud M. Ayoub 'Ulum al-Qur'ān: An Introduction to the Sciences of the Qur'ān. By Ahmad von Denffer Ibn Taymiyyah's Ethics—The Social Factor. By Victor E. Makari Shāh Wal?-Allāh And His Times. By Saiyid Athar Abbas Rizvi Islamic Theology and Philosophy: Studies in Honor of George F. Hourani. Edited by Michael E. Marmura Religion, My Own. The Literary Works of Naj?b Ma fūz. By Mattityahu Peled L'Orient dèchirè entre I'Est et L'Ouest (1955–1982). By Simon Jargy The Reflowering of Malaysian Islam: Modern Religious Radicals and Their Roots. By Judith Nagata Muslim Sects and Divisions. The section on Muslim sects in Kitāb al-Milal wa'I-Ni al by Mu ammad b. 'Abd al-Kar?m Shahrastān? (d. 1153). By A. K. Kazi and J. G. Flynn Muslim Intellectual Responses to “New Order” Modernization in Indonesia. By Muhammad Kamal Hassan Social history of Timbuktu: the role of Muslim scholars and notables 1400–1900. By Elias N. Saad Religion and Politics in Muslim Society: Order and Conflict in Pakistan. By Akbar S. Ahmed Baba of Karo: A Woman of the Muslim Hausa. By Mary F. Smith